Reducing Climate Risks by Improving Food Production and Value Chains: A Case of Sandy Soils in Semi-arid Kenya - Nkurunziza, Libère; Kuyah, Shem; Nyawira, Sylvia; Ng'ang'a, Stanley Karanja; Musei, Sylus; Chirinda, Ngonidzashe; Karugu, Winifred; Smucker, Alvin; Öborn, Ingrid (Frontiers in Climate, 2022)
Due to climate change, extreme weather events are becoming recurrent worldwide, causing significant reductions in agricultural production and food security. The livelihoods of smallholder farmers, especially those eking out a living by farming on sandy soils, are particularly affected. In this study, Makueni County, a semi-arid area with sandy soils in south-eastern Kenya, was used as a case study to pursue three objectives. First, using survey data from 203 households, we examined how smallholder farmers perceive extreme weather events that affect smallholder farmers and current management strategies to mitigate the consequences. Second, we used experimental data to illustrate the potential gains of implementing sub-surface water retention technology (SWRT) in the region. Third, we held group discussions with stakeholders in food value chains (FVC) to identify perceived ways and means of managing climate risks. The data showed that 199 out of 203 farmers surveyed had experienced an extreme event associated with climate change and variability during the last previous five years. Of these 199 farmers, 161 reported having changed their farming practices to adapt, especially to drought (70%) and increased temperature (22%). Common adaptation practices included early planting, reducing the area under cultivation, and water harvesting. Experimental data showed that using SWRT resulted in a 50%, 100%, 150%, and 170% increase in maize grain yield, cob number, cob weight, and maize stover biomass, respectively, compared with the control (without SWRT). Stakeholder group discussions along the FVC demonstrated a need for synergy among actors to mitigate climate risks caused by extreme weather events. These findings suggest that diversification of management strategies at farm level, combined with external inputs (new technologies, improved seeds, etc.) and services (credit access, learning from peers, and professionals) will be instrumental in reducing the climate risks to smallholder farmers. Improving access to viable markets and creating links with post-harvest actors in order to add value to basic food commodities can further increase the capacity of smallholder farmers to manage climate risks.